Evaluating county-level spatial prevalence and clustering of medicare beneficiaries in Mississippi. Issue 2 (June 2018) - Liew, Hui-Peng; Brooks, Talbot
Highlights: Counties assigned to two clusters are markedly different in terms of socioeconomic well-being but are somewhat similar in terms of disease distributions and healthcare utilization. Public health priorities should focus on addressing the geographic disparities in disease distribution and healthcare utilization that exist among the Mississippi counties. Medicare beneficiaries living in counties that are predominantly rural, predominantly Black, and/or have higher percentages of population living below the poverty level should be the targets. Abstract: Objective: This study seeks to examine how the extent of socioeconomic deprivation, racial and ethnic isolation, and health disadvantage differ among Medicare beneficiaries in Mississippi. Methods: Geographical information system (GIS) mappings are used in conjunction with cluster analysis to examine patterns of disparities in disease distribution, healthcare utilization and socioeconomic well-being among different counties in Mississippi. Results: Results reveal that counties in these two clusters are markedly different in terms of socio-economic well-being but are somewhat similar in terms of disease distributions and healthcare utilization. Conclusion: Addressing the geographic disparities in disease distribution and healthcare utilization that exist among the counties should be a public health priority. Specifically, health policies and programs should be renewed to target people living in counties that are either predominantly rural or predominantly Black or have higher percentages of population living below the poverty level.